MENJAGA KESEHATAN MATA PADA ERA TEKNOLOGI DAN ONLINE LEARNING DEMI VISI INDONESIA 2045 - Ferry Doringin; Murni Marlina Simarmata; Lorentius Wahana Dika (Akademi Refraksi Optisi dan Optometry Gapopin, 2021)
This paper aims to find important steps that must be taken by a number of parties to overcome the increase in cases of myopia in children. These steps are very urgent to be carried out in relation to cases of myopia which are growing very rapidly in children in this era of the Industrial Revolution 4.0. Using qualitative methods, this study explored a number of literatures and interviewed three experts who worked as lecturers at ARO Gapopin. The results of this study indicate that technology is closely related to the success of children in achieving Indonesia's Vision 2045 which is the golden generation related to the demographic bonus. Also, the increase in myopia is related to the myths that live in society that must be overcome. In addition, myopia can be overcome if the relevant parties have the knowledge and methods related to effective treatment.